The Role of Job Satisfaction Mediation in the Influence of Person-Job Fit and Job Training on Employee Performance at Grand Inna Kuta Hotel - Dewi, Luh Putu Alda Meysintia; Martadiani , Anak Agung Media; Suarka, Ida Bagus Komang (Formosa Journal of Applied Sciences, 2024)
The study aims to analyze how job satisfaction mediates the influence of person-job fit and job training on employee performance at Grand Inna Kuta Hotel. With a population of 158 employees, saturation sampling was used. Data collected via questionnaires were analyzed using SEM-PLS. Findings reveal: 1) Person-job fit positively but insignificantly influences employee performance, 2) Job training also positively but insignificantly affects employee performance, 3) Person-job fit significantly affects job satisfaction, 4) Job training significantly impacts job satisfaction, 5) Job satisfaction significantly boosts employee performance, 6) Job satisfaction mediates the relationship between person-job fit and employee performance, and 7) It also mediates the connection between job training and employee performance.